Eksistensi Lembaga Adat Adolang Sebelum Dan Setelah Pemekaran Wilayah - Muhammad Yusri AR; Najibullah Najibullah; Abdul Hafid; Hadi Yudho Prio Wibowo; Eni Susanti (Jayapangus Press, 2026)
This research analyzes the existence of Adolang Traditional Institution before and after territorial division in Pamboang Subdistrict, Majene Regency. The division of Adolang Village into four villages raised concerns about the continuity of traditional institutions as guardians of local cultural values. This descriptive-analytical qualitative research employed a a purposive sampling technique and collected data through in-depth interviews, observation, documentation, and literature review. The findings indicate that the existence of the Adolang Traditional Institution remains relatively stable, with no significant changes following territorial division. The traditional institution continues to exist due to the the Adolang community's awareness, the commitment of cultural activists, and the active role of traditional officials in preserving customs. Despite territorial fragmentation, cultural solidarity among the Adolang community is maintained through consistently implemented traditional activities. This research contributes to understanding the resilience of traditional institutions in facing structural changes in village governance during the regional autonomy era.